1996
DOI: 10.1002/(sici)1096-9063(199602)46:2<145::aid-ps327>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of fenvalerate after intravenous administration to sheep

Abstract: The pharmacokinetics of total radioactivity and of intact fenvalerate were determined in sheep treated intravenously with radiolabelled or nonradiolabelled fenvalerate. Mean residence times (MRT) of total radioactivity and intact fenvalerate in plasma were 910 (f 75) and 39 ( f 3) min, while harmonic mean elimination-phase half-lives (TM,) were 990 and 82 min, each respectively. Systemic clearance values (CI,) of total radioactivity and intact fenvalerate were 2.8 (k0.3) ml min-' kg-' and 51.3 (f5.9) ml min-' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Finally, an in vivo study conducted in Suffolk ewes and Hereford heifers (Danielson and Golsteyn, 1996) showed that the hepatic capacity to clear the CYP1A substrate caffeine from the systemic circulation is similar between the two species. However, the preferred routes of biotransformation differ, paraxanthin (mainly due to CYP1A2) being the major plasma metabolite in cattle, whereas theophylline was predominant in sheep, suggesting that sheep may express CYP1A2 to a lesser extent than cattle.…”
Section: Comparative Expression and Activity Of Cyp1 Enzymes In Sheep...mentioning
confidence: 99%
“…Finally, an in vivo study conducted in Suffolk ewes and Hereford heifers (Danielson and Golsteyn, 1996) showed that the hepatic capacity to clear the CYP1A substrate caffeine from the systemic circulation is similar between the two species. However, the preferred routes of biotransformation differ, paraxanthin (mainly due to CYP1A2) being the major plasma metabolite in cattle, whereas theophylline was predominant in sheep, suggesting that sheep may express CYP1A2 to a lesser extent than cattle.…”
Section: Comparative Expression and Activity Of Cyp1 Enzymes In Sheep...mentioning
confidence: 99%